2022
DOI: 10.1007/s00284-022-03107-w
|View full text |Cite
|
Sign up to set email alerts
|

Pal Affects the Proliferation in Macrophages and Virulence of Brucella, and as Mucosal Adjuvants, Provides an Effective Protection to Mice Against Salmonella Enteritidis

Abstract: The purpose of this study was to elucidate the roles of peptidoglycan-associated lipoprotein (Pal protein) in the proliferation of Brucella in macrophage and bacterial virulence, and to evaluate the immune effect of Pal protein to Salmonella enteritidis . Murine macrophage-like cell line Raw264.7 was stimulated by recombinant Pal protein, and the expression of TNF-α and IFN-γ were up-regulated, but not it of IL-1β and IL-6. The macrophages infection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…To evaluate the virulence of Δ pal at the animal infection level, this study measured LD 50 , bacterial loads in mouse organs, and histopathological changes, finding that the LD 50 of Δ pal is about 10 4 times greater than the wild type, indicating significantly reduced virulence of Δ pal ; and after infection for 24 h, 72 h, and 120 h, the bacterial loads in the spleen, liver, and cecum of the pal gene deletion strain were significantly lower than those of the wild type. Chen Y and others found that deletion of the pal gene in Brucella reduced bacterial colonization ability in the host spleen, consistent with this study ( Chen et al, 2022 ). Therefore, it can be confirmed that deletion of the pal gene weakens the colonization ability of S. enteritidis in host tissues, making it easier for the immune system to eliminate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To evaluate the virulence of Δ pal at the animal infection level, this study measured LD 50 , bacterial loads in mouse organs, and histopathological changes, finding that the LD 50 of Δ pal is about 10 4 times greater than the wild type, indicating significantly reduced virulence of Δ pal ; and after infection for 24 h, 72 h, and 120 h, the bacterial loads in the spleen, liver, and cecum of the pal gene deletion strain were significantly lower than those of the wild type. Chen Y and others found that deletion of the pal gene in Brucella reduced bacterial colonization ability in the host spleen, consistent with this study ( Chen et al, 2022 ). Therefore, it can be confirmed that deletion of the pal gene weakens the colonization ability of S. enteritidis in host tissues, making it easier for the immune system to eliminate.…”
Section: Discussionsupporting
confidence: 90%
“…Changes in the Tol-Pal system typically disrupt bacterial cell membrane integrity, disturb outer membrane permeability, and make bacteria more sensitive to antimicrobial peptides and detergents ( Godlewska et al, 2009 ). Studies on Burkholderia mallei ( Dyke et al, 2020 ), Brucella ( Chen et al, 2022 ), Haemophilus ducreyi ( Fortney et al, 2000 ), and Klebsiella pneumoniae ( Hsieh et al, 2013 ) show that deletion of the pal gene disrupts cell membrane integrity, reducing bacterial colonization ability in the host and affecting virulence. The pal gene is a conserved gene found in various bacteria, including Salmonella , but the function of the pal gene in S. enteritidis has not been clearly defined.…”
Section: Introductionmentioning
confidence: 99%